Implementasi E–Customer Relationship Management sebagai Penunjang Penerimaan Peserta Didik Baru di SMK Puspita Persada - Fawwaz Prabowo, Demas; Juanita, Safitri (INTERNAL (Information System Journal), 2024)
Competition between private schools in the Admission of New Students (PPDB) is intense, especially PPDB at Vocational High Schools (SMK). One of the private schools of PPDB, named Puspita Persada, is currently conducting an offline PPDB process, where new student admissions (CPDB) take and fill out the registration form offline at the school, as well as the distribution of school promotions in the form of the installation of banners and distribution of brochures in areas that are only around the school. Therefore, a study is needed to overcome problems in the PPDB process to increase the number of new student admissions and maintain parents' loyalty. Thus, this research applies the Electronic Customer Relationship Management (e-CRM) model to CPDB at SMK Puspita Persada. This research only focuses on 2 stages of CRM, namely acquire and retain. The research aims to integrate e-CRM on the website to improve the PPDB process by facilitating CPDB registration, offering discounts as a promotional tool, maintaining loyalty by allowing alumni reviews and facilitating criticism and suggestions. The methodology of this study uses the stages of the software development method named Prototyping. The results show that implementing e-CRM on the SMK Puspita Persada website to support the PPDB process can make it easier for schools to obtain CPDB by providing the most recent CPDB admission information feature, which can be read or downloaded.